China's Innovation Potential Support Instruments on the Example of Science and Technology Industrial Parks - Dziembała, Małgorzata (Instrumenty wspierania potencjału innowacyjnego Chin na przykładzie stref rozwoju przemysłowego zaawansowanych technologii, 2010)
The paper discusses China's trade in the aspect of high-tech products, which in the recent years records dynamic growth. It is also a result of the policy implemented by that country in the sphere of S&T assistance and in the building up of innovation potential. As part of that policy, there were set up science and technology industrial parks, inclusive of those at the state level. These parks develop rapidly, in terms of employment and industrial production volume, just like the number of firms that conduct in there their business activity. The STIPs and the TBIs became major elements of the innovation system which is currently established in China.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 326-338
Keywords: science and technology industrial parks; innovation